Architectural archives developing an appraisal, preservation, reference and access program for selected agencies in Metro Manila - Cansancio, Emmielouisa A. (2006)
Architectural archives are us, as a people and as a nation. These are indicative of the society's past, the simultaneous awareness and orientation of the present, and the directive guidance for the future. However, little does a society understand and appreciate that architectural archives exude more than an eloquent testimony of history than what a three-dimensional structure discloses. Ideally, the built and written evidences ought to exist together to completely document the built heritage. But societal priorities and considerations vary greatly, thereby causing turmoil to values placed over the built heritage. The architectural archives seriously suffer from neglect and in the inadequacies on their appraisal, preservation and access. Consequently, the society has taken a less active role in keeping architectural emblems - the same hold true with the architectural archives.